GAD65-positive autoimmune-associated epilepsy presenting with Ictal Hand Kissing; an uncommon presentation of a rare disease - Alia M.R. Fallatah; Hanan M. Abdulmutali; Majed H. Alhameed (Epilepsy & Behavior Reports, 2025)
Glutamic acid decarboxylase-65 (GAD65) is an enzyme responsible for the production of gamma-aminobutyric acid (GABA). Elevated levels of GAD65 antibodies have been recognized as a key biomarker of neurological autoimmune disorders, particularly autoimmune-associated epilepsy (AAE). We report the case of a 48-year-old woman with drug-resistant right temporal AAE, who initially developed seizures following a febrile illness accompanied by confusion. Notably, the patient exhibited rare ictal semiology involving stereotypical Ictal Hand kissing (IHK) behavior. Brain MRI revealed bilateral mesial temporal sclerosis (MTS), which was more pronounced on the right side. High serum titers of GAD65 antibodies further supported this diagnosis. This case underscores the incompletely elucidated clinical features of GAD65-positive AAE, and highlights the unique semiology of IHK behavior and its role in understanding and characterizing possible underlying epileptogenic networks.